Tertiary lymphoid structures in nasopharyngeal carcinoma: A multi-institutional study - Almangush, Alhadi; Ruuskanen, Miia; Hagström, Jaana; Kosma, Veli-Matti; Mäkitie, Antti A.; Leivo, Ilmo (Elsevier BV, 2025)
Background: Tertiary lymphoid structures (TLSs) associate with prognosis of many malignancies. However, the clinical significance of TLSs is not well-elucidated in nasopharyngeal carcinoma (NPC) patients.
Material and methods: In this whole population-based multicenter study, a total of 115 patients treated for NPC were included. The patients were treated at the five Finnish university hospitals. TLSs were assessed in routine hematoxylin and eosin (HE)-stained sections.
Results: Presence of TLSs associates significantly with improved survival in NPC. Absence of TLSs had a significant association with a poor disease-specific survival of NPC with a hazard ratio (HR) of 1.96 (95 % CI 1.09-3.53, P = 0.025) in the multivariable analysis. Similarly, absence of TLSs associated with worse overall survival with a HR of 1.68 (95 % CI 1.02-2.75, P = 0.040).
Conclusion: TLSs seem to be associated with prognosis of NPC patients. Having TLSs in NPC tumors correlates with good survival. The assessment of TLSs could aid in understanding the clinical behavior and in planning the treatment of NPC.